Annual report 2017: CGIAR Research Program on Rice - CGIAR Research Program on Rice (CGIAR Research Program on Rice, 2018)
This report contains the synthesis annual report for the CGIAR Research Program on Rice Agri-Food Systems (RICE). More detailed information, such as individual flagship project reports, center reports from nonCGIAR lead partners, capacity development statistics, publications, and listing of main partners can be found here. Updates on key outcome indicators can be accessed here. Also, more information on RICE can be accessed through its website ricecrp.org.